CHARACTERISTICS OF ZrO2 ADDED-MgAl2O4 CERAMICS FOR MATRIX OF INERT MATRIX NUCLEAR FUEL (IMF) - Dani Gustaman Syarif; Sylvia Hildayanti Hildayanti; R Henny Mulyani; Syoni Soepriyanto Soepriyanto (BATAN, 2011)
CHARACTERISTICS OF ZrO2 ADDED-MgAl2O4 CERAMICS FOR MATRIX OF INERTMATRIX NUCLEAR FUEL (IMF). Some ZrO2 added-MgAl2O4 ceramics for inert matrix of inertmatrix nuclear fuel (IMF) had been fabricated from powders prepared using precipitationmethod. Effect of ZrO2 addition on crystal structure, microstructure and mechanical properties ofthe ZrO2 added-MgAl2O4 ceramics was studied. The ceramics were prepared by mixing ZrO2,MgO and Al2O3 followed by pressing and sintering. The concentrations of ZrO2 additive were 0,5, 10 and 15 mole %. The mixed powder was pressed into green pellets with pressure of4 ton/cm2. The green pellets were sintered at 1600 oC for 2 hours in air. The sintered pelletswere evaluated visually. For microstructure examination, the fractured samples were examinedusing a scanning electron microscope (SEM). Crystal structure of the samples was analyzedusing x-ray diffraction (XRD). Hardness and fracture toughness of the sintered pellets weredetermined using microindentation method with aid of a Vickers microhardness tester fromZwick. It was known that the sintered pellets were visually good. The XRD data showed that theceramics crystallized in spinel cubic with second phase of ZrO2.. The hardness and fracturetoughness of the ceramics increased with the increase of ZrO2 concentration.